2002
DOI: 10.1023/a:1020611925819
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Atherosclerosis is a disease of the arteries in which fatty plaques develop on the inner arterial wall, which eventually obstructs blood flow. Identified risk factors for atherosclerosis include genetics, diet, lifestyle, smoking, circulating lipid and cholesterol levels, and molecular and circulating signals of chronic vascular inflammation. The link between flavonoids and atherosclerosis is based partly on the evidence that some flavonoids possess antioxidant properties and have been shown to be potent inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…The amount of supplemental dietary fat has ranged from 0 to 20% (w/w) [30,32,36,48,51,62,76-78,85,90,95-97], with 10% (w/w) used most frequently [31,33-35,37-43,45,47,50,52-56,59,63,65,66,79-84,88,92,94,98,99]. Ten percent saturated fatty acids (SFA) with supplemental cholesterol has been consistently reported to raise plasma total cholesterol and nHDL-C concentrations [31,38,47,50,55,62] without having adverse effects on hepatic function [51].…”
Section: Resultsmentioning
confidence: 99%
“…The amount of supplemental dietary fat has ranged from 0 to 20% (w/w) [30,32,36,48,51,62,76-78,85,90,95-97], with 10% (w/w) used most frequently [31,33-35,37-43,45,47,50,52-56,59,63,65,66,79-84,88,92,94,98,99]. Ten percent saturated fatty acids (SFA) with supplemental cholesterol has been consistently reported to raise plasma total cholesterol and nHDL-C concentrations [31,38,47,50,55,62] without having adverse effects on hepatic function [51].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, GSE supplementation decreased triglyceride and total cholesterol concentrations in serum and liver, and increased serum HDL-cholesterol and HDL-cholesterol/triglyceride ratio concentrations. Vinson et al (2002) reported a significant dose-dependent reduction in serum total cholesterol (TC) and triglyceride (TG) concentrations in an atherosclerosis model supplemented with GSE.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of seed extracts include: modulation of antioxidant enzymes expression (Puiggròs et al, 2005); protection against oxidative damage in brain cells of rats (Guo et al, 2007); atherosclerosis in hamsters (Vinson et al, 2002) and some anti-inflammatory effects (Wang et al, 2009). Due to grape seed has a considerable content of phenolic compounds (around 60 to 70% of the total of minority compound), in smaller percentages in other parts of the fruit, such as in peels (28-35%), and lower values are found in the pulp (approximately 10%) (Revilla et al, 1997).…”
Section: Grape Seed: An Agro-industrial Wastementioning
confidence: 99%